2019
DOI: 10.1111/ecin.12819
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Recreational Marijuana Legalization and Dispensing on Opioid Mortality

Abstract: This study documents how the changing legal status of marijuana has impacted mortality in the United States over the past two decades. We use a difference‐in‐difference approach to estimate the effect of medical marijuana laws (MML) and recreational marijuana laws (RML) on fatalities from opioid overdoses, and we find that marijuana access induces sharp reductions in opioid mortality rates. Our research corroborates prior findings on MMLs and offers the first causal estimates of RML impacts on opioid mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 42 publications
6
59
0
Order By: Relevance
“… 14 Another study examined the association between medical and recreational dispensaries with opioid related mortality rates, but at the state level. 4 This study found a negative association between the start of both types of cannabis dispensary operations within a state and opioid related mortality rates—an association that appears most pronounced with the class of opioids that includes fentanyl and its analogs. We reported consistent findings, but at the more fine grained county level and by using the prevalence of active dispensary operations rather than a single start date.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“… 14 Another study examined the association between medical and recreational dispensaries with opioid related mortality rates, but at the state level. 4 This study found a negative association between the start of both types of cannabis dispensary operations within a state and opioid related mortality rates—an association that appears most pronounced with the class of opioids that includes fentanyl and its analogs. We reported consistent findings, but at the more fine grained county level and by using the prevalence of active dispensary operations rather than a single start date.…”
Section: Discussionmentioning
confidence: 66%
“…However, some studies indicate that researchers should account for legal allowances for cannabis dispensary operations rather than focusing on the mere passage of cannabis laws; this provides a better reflection of the potential availability of legal cannabis and its association with opioid use within a geographical area. 4 5 8 These studies, which focus specifically on medical dispensaries, have found more consistent evidence of a negative association between statewide medical dispensary allowances and opioid related mortality rates. One study has modeled the association between medical cannabis dispensary presence and prescription opioid related death rates at the county level, and also found a negative association.…”
Section: Discussionmentioning
confidence: 98%
“…We use data on state RML effective dates collected by Chan, Burkhardt, and Flyr (2020), and ProCon.org to capture states' law environment, see Figure 1. We construct a variable coded one in state/quarter‐year pairs with an RML in place and coded zero in state/quarter‐year pairs when there is no RML 4…”
Section: Methodsmentioning
confidence: 99%
“… States that have adopted and not adopted a recreational marijuana use (RML) by 2020. Effective dates are based on legal statute information collected by Chan et al (2020) and http://ProCon.org. RML effective dates are as follows: Alaska: February 2015, California: November 2016, Colorado: December 2012, District of Columbia: February 2015, Illinois: January 2020, Maine: January 2017, Massachusetts: December 2016, Michigan: December 2018, Nevada: January 2017, Oregon: July 2015, Vermont: July 2018, and Washington: November 2012 …”
Section: Methodsmentioning
confidence: 99%
“…The economics literature has long recognized the importance of substitution patterns across drugs, showing fluid substitution in response to supply changes for alcohol, smoking, and marijuana. 14 We add to this literature by exploiting the introduction of abuse-deterrent OxyContin as a large national shock to the supply of abusable opioids to understand its ramifications for overdose deaths involving substitute drugs. The reformulation represents one of the largest disruptions to the nonmedical market for opioids and presents a rare opportunity to isolate the effects of consumer-level substitution from producer-level substitution (since the latter response is not possible in this context 15 ).…”
Section: Related Literature On Supply-side Drug Policymentioning
confidence: 99%